2004
DOI: 10.1023/b:caim.0000013158.15961.43
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of exercise induced myocardial ischemia in patients with isolated coronary artery ectasia

Abstract: The aim of this study was to investigate the angiographic predictors of exercise induced ischemia in patients with isolated coronary ectasia. We have prospectively analysed coronary angiograms of 1521 consecutive patients undergoing cardiac catheterisation. The overall incidence of coronary ectasia was 6.7% (102 patients). Forty-six patients (3%) with non-obstructive, diffuse or segmental coronary ectasia (i.e. isolated coronary ectasia) constituted the main study group. Coronary angiograms were reviewed for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…5). [29][30][31] The presence of reversible perfusion defects was described in myocardial scintigraphy. 25 Previous studies have shown that anterior wall abnormalities in particular are strongly associated with impaired LV twist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). [29][30][31] The presence of reversible perfusion defects was described in myocardial scintigraphy. 25 Previous studies have shown that anterior wall abnormalities in particular are strongly associated with impaired LV twist.…”
Section: Discussionmentioning
confidence: 99%
“…5). [29][30][31] The presence of reversible perfusion defects was described in myocardial scintigraphy. 27 Furthermore, decreased coronary flow reserves, in spite of having a patent coronary anatomy, were also observed in patients with CSF.…”
Section: Discussionmentioning
confidence: 99%
“…However, interestingly, it has been found that diabetes, which is considered to be equivalent to CAD, does not increase the frequency of CAE (17) . In histopathologic evaluation of CAE specimens, varying degrees of atrophy and destruction have been observed in the muscoelastic components of the muscularis media, and it has been found that the etiology is predominantly atherosclerosis in autopsy series (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) .…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest disruption in microvascular perfusion in myocardial segments supplied by ectatic arteries. It is thought that disruption of physiological coronary flow in ectasic segments increases thrombogenicity in this area and that distal embolization of the thrombi formed are significant causes of disruption in microvascular perfusion in patients with CAE (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CAE without stenosis had positive results during myocardial perfusion scintigraphic evaluation and treadmill exercise tests (37,78). In patients with isolated CAE, the extent of the ectasia, diffuse ectasia and backflow-phenomenon in an ectatic left anterior descending artery were identified as the most important angiographic predictors of ischemia on exercise testing (79).…”
Section: Clinical and Imaging Featuresmentioning
confidence: 99%